Efficacy and safety of the SGLT2 inhibitor empagliflozin versus placebo and the DPP-4 inhibitor linagliptin versus placebo in young people with type 2 diabetes (DINAMO): a multicentre, randomised, double-blind, parallel group, phase 3 trial. Issue 3 (March 2023) - Laffel, Lori M; Danne, Thomas; Klingensmith, Georgeanna J; Tamborlane, William V; Willi, Steven; Zeitler, Philip; Neubacher, Dietmar; Marquard, Jan; ,; Bardymova, Tatiana; Barrientos Perez, Margarita; Bethin, Kathleen; et al.
Summary: Background: The incidence of type 2 diabetes in young people is increasing, but treatments remain limited. We aimed to assess the efficacy and safety of an empagliflozin dosing regimen versus placebo and linagliptin versus placebo on glycaemic control in young people with type 2 diabetes. Methods: In this double-blind, placebo-controlled trial done in 108 centres in 15 countries, participants with type 2 diabetes (aged 10–17 years; HbA1c 6·5–10·5% [48–91 mmol/mol]) who had been previously treated with metformin or insulin were randomly assigned (1:1:1) to oral empagliflozin 10 mg, oral linagliptin 5 mg, or placebo. Participants in the empagliflozin group who did not have HbA1c below 7·0% (<53 mmol/mol) by week 12 underwent a second double-blinded randomisation (1:1) at week 14, either remaining on 10 mg or increasing to 25 mg. Participants in the placebo group were randomly reassigned (1:1:1) in a double-blinded manner at week 26 to linagliptin 5 mg or one of the empagliflozin doses (10 mg or 25 mg). Investigators were masked throughout the trial and received assignments of blinded medication kits through interactive response technology for all participants at the initial randomisation and for the re-randomisations at weeks 14 and 26. The primary outcome was change from baseline in HbA1c at 26 weeks. For empagliflozin, results were based on a pooled analysis for all participants on empagliflozin. Safety was assessed until week 52. This trial is registered with ClinicalTrials.gov, NCT03429543 . Findings: Between April 26, 2018, and May 26, 2022, of 262 screened participants, 158 (60%) were randomly assigned to treatment (53 [34%] to placebo, 52 [33%] to empagliflozin 10 mg, and 53 [34%] to linagliptin). For the primary outcome, the adjusted mean HbA1c change from baseline at week 26 was –0·84% [–9·2 mmol/mol] in the empagliflozin pooled group versus placebo (95% CI –1·50 to –0·19 [–16·4 to −2·1]; p=0·012); the corresponding change from baseline for linagliptin versus placebo was –0·34% [–3·8 mmol/mol; 95% CI –0·99 to 0·30 [–10·8 to 3·3]; p=0·29). Adverse events occurred in 34 (64%) participants in the placebo group, 40 (77%) in the empagliflozin pooled group, and 37 (71%) in the linagliptin group, up to week 26. Of these, severe adverse events were reported in two (4%) participants in the placebo group, one (2%) in the empagliflozin pooled group, and one (2%) in the linagliptin group. Hypoglycaemia was the most frequently reported adverse event with higher rates for those on active drug treatment compared with placebo. No severe hypoglycaemia cases were reported. Interpretation: Empagliflozin provided clinically relevant placebo-corrected reductions in HbA1c, whereas linagliptin did not, and might offer a new treatment option for young people with type 2 diabetes. Funding: The Boehringer Ingelheim and Eli Lilly and Company Alliance.